2013
DOI: 10.1002/lary.23862
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of long‐term results of nasal tip defatting in rhinoplasty cases

Abstract: Defatting techniques have no effect on reducing tip and supratip skin thickness after rhinoplasty in moderate to thick skins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Many intraoperative and postoperative methods have been described in the literature to avoid supratip fullness. [3][4][5]8,18,19 Although investigators have achieved a consensus of opinion on most postrhinoplasty practice patterns, PRT and its effects are fairly unknown and not studied in terms of evidencebased medicine. 20 Hoefflin 9(p375) was the first investigator to report the effect of PRT with the following: "4 to 6 weeks of nighttime postoperative nasal taping will help decrease swelling, and will give patients something to do."…”
Section: Discussionmentioning
confidence: 99%
“…Many intraoperative and postoperative methods have been described in the literature to avoid supratip fullness. [3][4][5]8,18,19 Although investigators have achieved a consensus of opinion on most postrhinoplasty practice patterns, PRT and its effects are fairly unknown and not studied in terms of evidencebased medicine. 20 Hoefflin 9(p375) was the first investigator to report the effect of PRT with the following: "4 to 6 weeks of nighttime postoperative nasal taping will help decrease swelling, and will give patients something to do."…”
Section: Discussionmentioning
confidence: 99%
“…1,23 Excessive defatting and thinning of the skin is a very risky procedure that may result in irreversible complications as skin atrophy and necrosis. Additionally, Wright 20 and Nemati et al 24 showed that the skin defatting failed to guard against pollybeak formation. In our study, skin defatting was limited to the loose fibrofatty tissue and no attempt was made to thin the actual dermis.…”
Section: Discussionmentioning
confidence: 99%
“…Different measuring mechanisms have been used, including sonograms and computed tomography with varying results. [5][6][7] Other authors have proposed different skin evaluations where skin texture and characteristics are evaluated as well as skin thickness. 8,9 All of these quantitative methods could eventually aid the surgeon in planning a surgical approach or in evaluating surgical or minimally invasive procedures on the skin, but results are not conclusive.…”
Section: The Skin Evaluationmentioning
confidence: 99%